Kantika Ngara Practice: Marriage Validity under Islamic and Positive Law in Ambalawi Regency Local Wisdom - Hidayatullah, Syarif; Zia Ulhaq, Muhammad; Fitriani (Yayasan Lembaga Studi Makwa, 2025)
This study examines the practice of Kantika Ngara in Ambalawi Subdistrict, Bima Regency, a local pre-marital tradition involving the symbolic adjustment of the bride’s and groom’s names, which is believed to bring harmony, prosperity, and blessings to married life. The purpose of this research is to describe the implementation of Kantika Ngara, analyze it from the perspectives of Islamic law and positive law, and assess the harmony between religious norms, state regulations, and local wisdom. This study employs a qualitative approach using normative and empirical methods. Data were collected through observation, in-depth interviews, and documentation, and analyzed using NVivo to identify key themes. The findings show that Kantika Ngara is practiced through symbolic methods such as counting name letters, interpreting names, observing palm lines, and measuring finger length as indicators of fortune. From the perspective of Islamic law, this tradition does not invalidate the marriage contract because the name adjustment is symbolic and does not affect legal identity. From the perspective of positive law, the practice does not cause administrative or legal problems since official identities remain unchanged. This study demonstrates that Kantika Ngara represents local wisdom that harmonizes religious values, state law, and community culture, contributing to discussions on legal pluralism and cultural accommodation